Prevalence of COVID-19 fear and its association with quality of life and network structure among Chinese mental health professionals after ending China’s dynamic zero-COVID policy: a national survey - Lam, Mei Ieng; Chen, Pan; Zhang, Qinge; Sha, Sha; An, Feng-Rong; Su, Zhaohui; Cheung, Teris; Ungvari, Gabor S.; Ng, Chee H.; Xiang, Yu-Tao; Feng, Yuan (Frontiers in Public Health, 2023)
Background: China recorded a massive COVID-19 pandemic wave after ending its Dynamic Zero-COVID Policy on January 8, 2023. As a result, mental health professionals (MHPs) experienced negative mental health consequences, including an increased level of fear related to COVID-19. This study aimed to explore the prevalence and correlates of COVID-19 fear among MHPs following the end of the Policy, and its association with quality of life (QoL) from a network analysis perspective.Methods: A cross-sectional national study was conducted across China. The correlates of COVID-19 fear were examined using both univariate and multivariateanalyses. An analysis of covariance (ANCOVA) was conducted to determine the relationship between fear of COVID-19 and QoL. Central symptoms were identified using network analysis through the "Expected Influence" of the network model while specific symptoms directly correlated with QoL were identified through the "flow function".: A total of 10,647 Chinese MHPs were included. The overall prevalence of COVID-19 fear (FCV-19S total score ≥16) was 60.8% (95% CI=59.9-61.8%). The binary logistic regression analysis found that MHPs with fear of COVID-19 were more likely to be married (OR=1.198; P<0.001) and having COVID-19 infection (OR=1.235; P=0.005) and quarantine experience (OR=1.189; P<0.001). Having better economic status (good versus poor: OR=0.479; P<0.001; fair versus poor: OR=0.646; P<0.001) and health status (good versus poor: OR=0.410; P<0.001; fair versus poor: OR=0.617; P<0.001) were significantly associated with a lower risk of COVID-19 fear. The ANCOVA showed that MHPs with fear of COVID-19 had lower QoL (F (1,008) =228.0, P<0.001). "Palpitation when thinking about COVID-19" was the most central symptom in the COVID-19 fear network model, while "Uncomfortable thinking about COVID-19" had the strongest negative association with QoL (average edge weight=-0.048). Conclusion: This study found a high prevalence of COVID-19 fear among Chinese MHPs following the end of China's Dynamic Zero-COVID Policy. Developing effective prevention and intervention measures that target the central symptoms as well as 4 symptoms correlated with QoL in our network structure would be important to address COVID-19 fear and improve QoL.